Simulation and multi-scenario prediction of land-use change in the Gansu section of the Yellow River Basin, China - Ma, Xin; Li, Jie; Li, Guang (Frontiers in Environmental Science, 2024)
Introduction] Gansu section of the Yellow River Basin is an important water resource conservation and replenishment area for the entire Yellow River Basin. With urbanization and socioeconomic development, it is urgent to study the characteristics of land use change and its future simulation in order to realize the coordinated ecological and economic development. [Methods] Based on the Patch-generating Land use Simulation (PLUS) Model, this paper investigated the main drivers of land use type expansion with comprehensive consideration for natural and socioeconomic aspects, moreover, simulated land use change in 2030 under four scenarios of natural development, cultivated land protection, ecological priority and economic construction. [Results]The results showed that: (1) The prediction of land use types continued the historical evolution since 1980. Grassland, cultivated land and forest land were still dominant land types, accounting for more than 87% of the basin's total area. Waters and wetlands remained relatively stable, and there was an obvious increase of about 20% in construction land. (2) Construction land and grassland was primarily driven by the social factor of the distance from the primary road and the distance from second road respectively. Cultivated land was greatly affected by the economic factor of population density. (3) Cultivated land protection scenario was the only one of the four scenarios that can make cultivated land area increase positively, with increase rate of 0.5%. This scenario also restricted effectively the conversion of cultivated land into construction land. Ecological priority scenario can expand grassland obviously with a proportion of 1.82% and slow down oasis desertion. Economic construction scenario can make construction land area increase the most by a rate of 25.5% to accelerate the economic development of specific regions in the study area. [Discussion] Therefore, Implementing policies on the basis of choosing suitable scenario in different areas was significant for optimizing land use structure, promoting the efficient use of land resources and ecological environment in Gansu section of the Yellow River Basin.